Suitability of Computer-Assisted Analysis of Semen from Mithun - Perumal, P. (International Journal of Bio-resource and Stress Management, 2017)
The assessment of sperm motility using the conventional microscopical methods is difficult and subjective. High variations have been reported for the estimation of motility parameters of the same ejaculates. Computer assisted semen analysis (CASA) is an accurate technique used for the assessment of the motility and velocity parameters of mithun semen. High number of spermatozoa can be analysed individually in a short period of time. The present study was investigated to assess the motility and velocity parameters of sperm of good and poor quality semen by computer assisted sperm analyser (CASA). Fifty ejaculates were collected from ten matured mithun bulls and were splited into good (n=25) and poor (n=25) quality based on the individual motility and mass activity, i.e. 60% and above and 2.5 and above, respectively were considered as good quality whereas less than 60% and 2.5, respectively were considered as poor quality ejaculates. CASA parameter such as forward progressive motility (FPM; %), non-progressive motility (NPM; %), total motility (TM; %), static sperms (SM; %), curvilinear velocity (VCL; μm/sec), average path velocity (VAP; μm/sec), straight line velocity (VSL; μm/sec), linearity (LIN; %), straightness (STR; %), amplitude of lateral head displacement (ALH; μm), wobble (WOB; %) and beat cross frequency (BCF; Hz) were measured by CASA analyser. Result shown that these parameters varied significantly (p<0.05) between the good and poor quality semen and good quality semen has significantly (p< 0.05) higher value than poor quality ejaculates. It was concluded that good quality sperm has higher functional sperm structures to mobilise forward direction and faster to achieve the successful fertilization.